(untitled) (Perner’s Contacts, 2013)
Within the research project itself, the detailed literature review focusing on global research projects together with those available at the PortEconomics academics initiative will be supplemented with local and regional information and research sources. The research key objective is to assess factors that could help mitigate bottlenecks within CEE logistics platforms and the Czech Republic in particular.